Spectrophotometric Determination of Sulfamethoxazole Based on Charge-Transfer Complexation with Sodium Nitroprusside - Mahmoud, Tariq Y.; Dikran, Sarmad B.; Mohammed, Alaa K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A simple, accurate and precise spectrophotometric method has been developed for the analysis of sulfamethoxazole (SMZ) in pure form and pharmaceutical preparation. The method involves a direct charge transfer complexation of sulfamethoxazole (SMZ) with sodium nitroprusside (SNP) in alkaline medium and the presence of hydroxyl amine hydrochloride. Variables affecting the formation of the formed orange colored complex were optimized following two approaches univariate and central composite experimental design (CCD) multivariate. Under optimum recommended conditions, the formed complex exhibits Î»max at 512 nm and the method conforms Beer’s law for SMZ concentration in the range of 5.0-150.0 (Âµg.mL-1) with molar absorptivity 1.139Ã—103 L.mol-1.cm-1, and r = 0.9997. Analysis of SMZ pharmaceutical dosages shows a good agreement with the real amounts.